Factors Influencing Adaptation and Performance at Physical Exercise in Complex Congenital Heart Diseases after Surgical Repair. (15th April 2014) - Bassareo, P. P.; Saba, L.; Solla, P.; Barbanti, C.; Marras, A. R.; Mercuro, G.
Abstract : In the last thirty years, steady progress in the diagnostic tools and care of subjects affected by congenital heart diseases (CHD) has resulted in a significant increase in their survival to adulthood, even for those affected by complex CHD. Based on these premises, a number of teenagers and adults affected by corrected (surgically or through interventional techniques) CHD ask to be allowed to undertake sporting activities, both at a recreational and competitive level. The purpose of this review is to examine the mechanisms influencing the adaption at physical exercise of patients suffering from complex CHD. The conclusion is that even if there are some modest risks with exercise, they should be seen in perspective, and the life-long benefits of regular exercise on general health, mood, and well-being should be emphasized.